Intermittent hypoxic training. A pilot study - Hellemans, J. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
Ten endurance athletes were tested with the method of intermittent hypoxic training (IHT) in relation to haematological factors and performance over a period of three weeks. Results show an overall improvement in haematological factors related to oxygen transport and performance. The results indicate that IHT is an effective method to simulate altitude training. On the basis of the results it is recommended that further research and testing is done in the area of maximising outcome for individual athletes. However, in general the method of IHT can be strongly recommended for any serious athlete as part of their training and preparation.